2017
DOI: 10.1152/ajpregu.00482.2016
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 knockout protects against diabetes-mediated changes in cerebral perfusion and cognitive deficits

Abstract: The risk of cognitive decline in diabetes (Type 1 and Type 2) is significantly greater compared with normoglycemic patients, and the risk of developing dementia in diabetic patients is doubled. The etiology for this is likely multifactorial, but one mechanism that has gained increasing attention is decreased cerebral perfusion as a result of cerebrovascular dysfunction. The innate immune system has been shown to play a role in diabetic vascular complications, notably through the Toll-like receptor (TLR)-stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…The protein encoded by TLR2 is a member of the tolllike receptor (TLR) family, whose members are significant pattern recognition receptors of the innate immune system, initiating inflammatory cascades by recognizing pathogen-and damaged-associated molecular patterns. TLR2 was found to play a pivotal role in inflammation after ischemic brain injury (Wang et al, 2011) and was involved in the development of diabetic microvascular complications, including endothelial dysfunction and cognitive impairment (Hardigan et al, 2017). In this study, we found that TLR2 was upregulated in the VaD samples compared with the controls samples, which supports the previous results.…”
Section: Discussionsupporting
confidence: 89%
“…The protein encoded by TLR2 is a member of the tolllike receptor (TLR) family, whose members are significant pattern recognition receptors of the innate immune system, initiating inflammatory cascades by recognizing pathogen-and damaged-associated molecular patterns. TLR2 was found to play a pivotal role in inflammation after ischemic brain injury (Wang et al, 2011) and was involved in the development of diabetic microvascular complications, including endothelial dysfunction and cognitive impairment (Hardigan et al, 2017). In this study, we found that TLR2 was upregulated in the VaD samples compared with the controls samples, which supports the previous results.…”
Section: Discussionsupporting
confidence: 89%
“…In order to assess cognitive deficits, we used the NOR test (Hardigan et al, 2017; Prakash et al, 2013b). Animals were habituated to test apparatus in a grey plastic box (63L × 38W × 42H cm) that was layered with animal bedding for 4 days prior to baseline testing for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental models have also shown diabetes-mediated temporal and spatial alterations in CBF. In STZ-induced T1D model, CBF is lower early in the disease process whereas the same model later shows increased perfusion (111) (Fig. 8).…”
Section: Cbfmentioning
confidence: 95%